20(S)-Protopanaxadiol blocks cell cycle progression by targeting epidermal growth factor receptor. (January 2020) - Zhang, Tiehua; Liang, Yuan; Zuo, Peng; Jing, Siyuan; Li, Tiezhu; Wang, Yongjun; Lv, Chengyu; Li, Da; Zhang, Jie; Wei, Zhengyi
Abstract: 20( S )-Protopanaxadiol [20( S )-PPD], one of the metabolites of ginsenosides, was investigated to determine its potential mechanism for targeting to epidermal growth factor receptor (EGFR) pathway in lung cancer cell A549. Results of kinase inhibitory assay showed that 20( S )-PPD was an EGFR tyrosine kinase inhibitor. By binding to EGFR, 20( S )-PPD disrupted the EGFR/MAPK signaling. The expression of genes in the pathway was altered and the upregulation of Ras and MEK1 was extremely notable. The accumulation and phosphorylation of EGFR, Ras, BRAF, Raf-1, MEK, and ERK were variously altered. The above alteration subsequently resulted in cell cycle arrest. 20( S )-PPD interfered the cell cycle regulation network and eventually blocked cell cycle progression at G0/G1 phase, which may be the key reason for proliferation inhibition. Although some apoptosis related genes and proteins were influenced, apoptosis was not the main reason for proliferation inhibition. The cell wound healing assay confirmed that the inhibition of 20( S )-PPD to A549 cells could suppress the migration and invasion thereof. The results of molecular docking and molecular dynamics simulation provide a possible interaction mechanism between EGFR and 20( S )-PPD. The results described above suggested that 20( S )-PPD could block cell cycle progression by targeting the EGFR/MAPK signaling pathway. Highlights: 20( S )-PPD is an EGFR tyrosine kinase inhibitor. 20( S )-PPD blocks the EGFR/MAPK pathway in A549 cells. 20( S )-PPD arrests the cell cycle at G0/G1 phase. The molecular basis for the binding of 20( S )-PPD to EGFR is explored.